Acerca do sujeito, da pessoa e do Direito nos Grundrisse; On subject, Person and Law in Grundrisse - Sartori, Vitor (Sofia, 2022)
No presente artigo, a partir daquilo que o filósofo brasileiro José Chasin chamou de análise imanente, abordaremos o Direito nos Grundrisse, procurando demonstrar que a crítica pachukaniana ao Direito – ao relacionar forma jurídica e a forma mercadoria – traz aspectos essenciais para a compreensão da posição de Marx sobre a esfera jurídica. Porém, a análise do autor alemão é mais ampla, e destaca também a ligação das relações jurídicas com aspectos essenciais da forma dinheiro, bem como da esfera da distribuição. Outra questão de grande importância é que a crítica marxiana tem um tratamento mais detido que aquela de Pachukanis tanto sobre a autonomização do Direito quanto no que diz respeito à correlação entre a lei do valor, a formação de sujeitos na sociedade capitalista e as categorias jurídicas. Abstract In this article, with José Chasin´s Immanent analysis, we will analyze Law in the Grundrisse, intending to demonstrate that Pachukan’s criticism of Law - relating legal form and form of commodity - brings essential aspects for the understanding of Marx’s position on the juridical sphere. However, an analysis by the German author is more comprehensive and allow us to link legal relationships with essential aspects of the money form, as well as of distribution. Another issue of great importance is the Marxian criticism that deals with a treatment more careful than the pachukanian of both, the autonomy, and the correlation between a law of value, the formation of Subjects in capitalist society and juridical categories. In this sense, we will bring a different approach to the hegemonic one in Brazil, represented by the Pachukanian tradition. We try to demonstrate that, even in the Grundrisse, in which the notion of subject and person are more recurrent, there is not an identification between these categories and the notion of subject of rights, always highlighted by authors such as Márcio Naves and Alysson Mascaro, as well as by their followers, as something central to the Marxist critique of Law.